2015
DOI: 10.1371/journal.pone.0132710
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Mediated Metastasis: Immune Induced Epithelial-To-Mesenchymal Transition in Inflammatory Breast Cancer Cells

Abstract: Inflammatory breast cancer (IBC) is the most insidious form of locally advanced breast cancer; about a third of patients have distant metastasis at initial staging. Emerging evidence suggests that host factors in the tumor microenvironment may interact with underlying IBC cells to make them aggressive. It is unknown whether immune cells associated to the IBC microenvironment play a role in this scenario to transiently promote epithelial to mesenchymal transition (EMT) in these cells. We hypothesized that solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 52 publications
3
79
0
1
Order By: Relevance
“…Our results are also in keeping with other recent studies that profiled the importance of macrophages in IBC404142. Cohen et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are also in keeping with other recent studies that profiled the importance of macrophages in IBC404142. Cohen et al .…”
Section: Discussionsupporting
confidence: 93%
“…Cohen et al . studied the epithelial-mesenchymal transition in IBC cell lines and found IL-6 to be one essential driver of the transition as measured by qRT-PCR of a standard gene panel40. Mohamed et al .…”
Section: Discussionmentioning
confidence: 99%
“…Upon obstructing lymphatic vessels, tumor emboli prevent proper drainage of the lymph fluid, causing skin reddening and painful swelling of breast tissue (Vermeulen et al , 2010; Lehman et al , 2013). IBC cells display high ALDH positivity, express high levels of E-cadherin, and interestingly, continue to express elevated levels of epithelial cell markers like E-cadherin, while gaining mesenchymal and stem-like characteristics (Nguyen et al , 2006; Charafe-jauffret et al , 2010; Cohen et al , 2015). In addition, activation of anti-apoptotic and antioxidant signaling cascades allow the IBC cells to survive in the presence of various cell death signals, leading to therapeutic resistance (Thomas et al , 2011; Allensworth et al , 2013; Williams et al , 2013; Price et al , 2015; Evans, 2016).…”
Section: Various 3d Culture Models Of Tumormentioning
confidence: 99%
“…In addition, expression of IL-4 and IL-17 found to indirectly induce bronchial-EMT via synergized action with TGF-β1 [39]. Furthermore, a study showed that the combination of TNF-α, IL-6, and TGF-β and cytokines released by activated immune cells augment aggressiveness of inflammatory breast cancer cells via the EMT process [40]. These data support our present results that a synergism among the secreted cytokines of TALs isolated from pLNs breast cancer patients stimulates the EMT program.…”
Section: Discussionmentioning
confidence: 99%